Highly Sensitive Temperature Sensor Based on Coupled-Beam AlN-on-Si MEMS Resonators Operating in Out-of-Plane Flexural Vibration Modes - Cheng Tu; Ming-hong Yang; Zi-qiang Zhang; Xiu-mei Lv; Lei Li; Xiao-Sheng Zhang (Research, 2022)
This paper reports a type of highly sensitive temperature sensor utilizing AlN-on-Si resonators with coupled-beam structures of double- and triple-ended-tuning-fork (D/TETF). For both resonators, the out-of-plane flexural mode is adopted as it favors the effect of thermal mismatch between the composite layers inherent to the AlN-on-Si structure and thus helps attain a large temperature coefficient of resonant frequency (TCF). The analytical model to calculate TCF values of D/TETF AlN-on-Si resonators is provided, which agrees well with the finite-element simulation and experimental results. The resonant temperature sensor is built by closing the loop of the AlN-on-Si resonator, a transimpedance amplifier, a low-pass filter, and a phase shifter to form an oscillator, the output frequency of which shifts proportionally to the ambient temperature. The measured sensitivities of the temperature sensors using D/TETF resonators are better than -1000 ppm/°C in the temperature range of 25°C~60°C, showing great potential to fulfill the on-chip temperature compensation scheme for cofabricated sensors.